2007
DOI: 10.1109/tsp.2006.882076
|View full text |Cite
|
Sign up to set email alerts
|

Kernels and Multiple Windows for Estimation of the Wigner-Ville Spectrum of Gaussian Locally Stationary Processes

Abstract: Abstract-This paper treats estimation of the Wigner-Ville spectrum (WVS) of Gaussian continuous-time stochastic processes using Cohen's class of time-frequency representations of random signals. We study the minimum mean square error estimation kernel for locally stationary processes in Silverman's sense, and two modifications where we first allow chirp multiplication and then allow nonnegative linear combinations of covariances of the first kind. We also treat the equivalent multitaper estimation formulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…A common approach is to select the window based on minimizing the effective time-frequency area occupied by a given component [61], [62]. Other authors [46], [47], [53] and [63] even propose the use of separated kernels, with different parameters at different times. An open issue remains about how to measure the performance of the selected window.…”
Section: A Choice Of the Type Of The Synthesis Windowmentioning
confidence: 99%
“…A common approach is to select the window based on minimizing the effective time-frequency area occupied by a given component [61], [62]. Other authors [46], [47], [53] and [63] even propose the use of separated kernels, with different parameters at different times. An open issue remains about how to measure the performance of the selected window.…”
Section: A Choice Of the Type Of The Synthesis Windowmentioning
confidence: 99%
“…The locally stationary process approach [16,17], where the covariance function of a nonstationary process is defined by…”
Section: Bandlimited White Noisementioning
confidence: 99%
“…Several methods have been proposed for WVS estimation, such as: the multitaper method [2] and the mean square error (MSE) optimal kernel method [3], which is proposed for the class of Gaussian harmonizable processes. Moreover, in [4], it is shown that the WVS can be estimated as a weighted sum of spectrograms; also, the WVS can be approximated by a set of Hermite functions for the class of locally stationary processes. Such an approximation is advantageous when it comes to calculation, since only a limited number of Hermite functions need to be calculated [5].…”
Section: Introductionmentioning
confidence: 99%